2022
DOI: 10.3389/frph.2022.1040640
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in utilization of a feminist telehealth abortion service in Brazil: A multilevel analysis

Abstract: The disruption caused by the COVID-19 pandemic on health services around the world boosted interest over telehealth models of care. In Brazil, where abortion is heavily restricted, abortion seekers have long relied on international telehealth services to access abortion pills. We conducted a cross-sectional multilevel study to assess the effect of individual and contextual social factors on utilization of one such service. For the individual-level, we analyzed data from the records of abortion seekers contacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Care providers felt that telemedicine increased access to medication abortion, facilitated a more user-centered approach, and reduced long-distance traveling time by both patients and physicians. Although telemedicine is believed to make abortion services more accessible, the study conducted in Brazil revealed inequalities in the utilization of abortion services via telemedicine across various regions, which varied based on income, and among different racial groups 47 . Given that provision of services via telemedicine requires access to advanced technologies such as high internet speed, populations who lack reliable internet access or who lack knowledge and education about the use of these technologies could be disproportionally affected by limited ability to utilize the service.…”
Section: Discussionmentioning
confidence: 99%
“…Care providers felt that telemedicine increased access to medication abortion, facilitated a more user-centered approach, and reduced long-distance traveling time by both patients and physicians. Although telemedicine is believed to make abortion services more accessible, the study conducted in Brazil revealed inequalities in the utilization of abortion services via telemedicine across various regions, which varied based on income, and among different racial groups 47 . Given that provision of services via telemedicine requires access to advanced technologies such as high internet speed, populations who lack reliable internet access or who lack knowledge and education about the use of these technologies could be disproportionally affected by limited ability to utilize the service.…”
Section: Discussionmentioning
confidence: 99%